الاستفادة من الصبغة الطبيعية المستخلصة من نبات التمر الهندي في صناعة أقمشة التريكو المستخدمة في عمل ملابس الأطفال - السيد، نهى محمد عبده; شريف، فوزي سعيد ذكي (جامعة المنيا - كلية التربية النوعية, 2021)
للأقمشة القطنية أهمية كبيرة في حياتنا اليومية نظرا لاستخداماتها المختلفة ومن أهمها استخدامها في صناعة ملابس الأطفال. فهي من الخامات التي تعطي إحساس بالراحة والنعومة للأطفال فضلا عن امتصاص العرق وتسمح أيضا بتبخره الهواء وكذلك قدرتها على التقليل من نمو البكتريا والفطريات على ثنايا الجلد. ومما لا شك فيه أن ملابس الأطفال من الملابس التي تحتاج إلى عمليات صباغة مختلفة للحصول على ألوان متعددة ومن أهم هذه الصبغات هي الصبغات الطبيعية وهي الأكثر أمانا على جلد الطفل حيث خلوها من المواد الكيميائية الضارة، وتتضح مشكلة البحث من خلال "دراسة كفاءة الخواص اللونية للصبغة الطبيعية المستخلصة من نبات التمر الهندي". حيث تعتمد أهمية البحث على مدى تأثير كفاءة الصبغة الطبيعية المستخلصة من نبات التمر الهندي على عمق اللون وخواص الثبات للأقمشة المصبوغة ويهدف البحث إلى التوصل إلى أفضل أنواع وتركيزات للمواد المستخدمة في صباغة أقمشة التريكو (قطن) بصبغة التمر الهندي الطبيعية، حيث أعطى التركيز 45 جم للصبغة أعلى قيمه لعمق اللون بقيمه 171.13 وأعطى التركيز 25 جم أقل قيمه لعمق اللون وكانت 83.16 وذلك باستخدام مثبت كبريتات الحديدوز بتركيز 10 جم، وأعطى المثبت كبريتات النحاس أقل قيمه لعمق اللون بقيمه 89.1 كما أعطى تركيز الصبغة 45 جم والمثبتة بكبريتات الحديدوز بتركيز 35 جم أعلى قيمه لعمق اللون بقيمه 257.22 وأعطى التركيز 15 جم للمثبت كبريتات الحديدوز أقل قيمه لعمق اللون وكانت 189.6 وذلك باستخدام نفس تركيز الصبغة.
Cotton fabrics are of great importance in our daily life due to their various uses, the most important of which is their use in the manufacture of children's clothes. It is one of the raw materials that give a feeling of comfort and softness to children as well as absorb sweat and also allow the evaporation of the air as well as its ability to reduce the growth of bacteria and fungi on the folds of the skin. There is no doubt that children's clothes are clothes that require different dyeing processes to obtain multiple colors, and the most important of these dyes are natural dyes, which are the safest on the child's skin as they are free from harmful chemicals and the research problem is evident through the study of the efficiency of the color properties of the natural dye Extracted from the tamarind plant. Where the importance of the research depends on the effect of the efficiency of the natural dye extracted from the tamarind plant on the depth of color and the stability properties of the dyed fabrics. The research aims to reach the best types and concentrations of materials used in dyeing knitted fabrics (cotton) with the natural tamarind dye, where the concentration was given to 45 g of the dye higher. The value of the color depth was 171.13 and the concentration of 25 g was given the lowest value for the color depth and it was 83.16, using a fixative ferrous sulfate at a concentration of 10 g, and the fixer gave copper sulfate the lowest value for the color depth with a value of 89.1. With a value of 257.22, a concentration of 15 gm was given to stabilizer ferrous sulfate the lowest value for color depth was 189.6, using the same concentration of dye.
Keywords: صناعة الأقمشة -- الصبغات الطبيعية -- أقمشة التريكو -- ملابس الأطفال